Methotrexate-loaded four-arm star amphiphilic block copolymer elicits CD8+ T cell response against a highly aggressive and metastatic experimental lymphoma - Hira S.K.; Ramesh K.; Gupta U.; Mitra K.; Misra N.; Ray B.; Manna P.P. (My University, 2025)
We have synthesized a well-defined four-arm star amphiphilic block copolymer [poly(DLLA)-b-poly(NVP)]4 [star-(PDLLA-b-PNVP)4] that consists of d,l-lactide (DLLA) and N-vinylpyrrolidone (NVP) via the combination of ring-opening polymerization (ROP) and xanthate-mediated reversible addition-fragmentation chain transfer (RAFT) polymerization. Synthesis of the polymer was verified by 1H NMR spectroscopy and gel permeation chromatography (GPC). The amphiphilic four-arm star block copolymer forms spherical micelles in water as demonstrated by transmission electron microscopy (TEM) and 1H NMR spectroscopy. Pyrene acts as a probe to ascertain the critical micellar concentration (cmc) by using fluorescence spectroscopy. Methotrexate (MTX)-loaded polymeric micelles of star-(PDLLA15-b-PNVP10)4 amphiphilic block copolymer were prepared and characterized by fluorescence and TEM studies. Star-(PDLLA15-b-PNVP10)4 copolymer was found to be significantly effective with respect to inhibition of proliferation and lysis of human and murine lymphoma cells. The amphiphilic block copolymer causes cell death in parental and MTX-resistant Dalton lymphoma (DL) and Raji cells. The formulation does not cause hemolysis in red blood cells and is tolerant to lymphocytes compared to free MTX. Therapy with MTX-loaded star-(PDLLA15-b-PNVP10)4 amphiphilic block copolymer micelles prolongs the life span of animals with neoplasia by reducing the tumor load, preventing metastasis and augmenting CD8+ T cell-mediated adaptive immune responses. © 2015 American Chemical Society.